Association of Clinical, Imaging, and Thrombus Characteristics With Recanalization of Visible Intracranial Occlusion in Patients With Acute Ischemic Stroke - Menon, Bijoy K; Al-Ajlan, Fahad S; Najm, Mohamed; Puig, Josep; Castellanos, Mar; Dowlatshahi, Dar; Calleja, Ana; Sohn, Sung-Il; Ahn, Seong H; Poppe, Alex; Mikulik, Robert; Asdaghi, Negar; et al. (JAMA, 2018)
IMPORTANCE: Recanalization of intracranial thrombus is associated with improved clinical outcome in patients with acute ischemic stroke. The association of intravenous alteplase treatment and thrombus characteristics with recanalization over time is important for stroke triage and future trial design. OBJECTIVE: To examine recanalization over time across a range of intracranial thrombus occlusion sites and clinical and imaging characteristics in patients with ischemic stroke treated with intravenous alteplase or not treated with alteplase. DESIGN, SETTING, AND PARTICIPANTS: Multicenter prospective cohort study of 575 patients from 12 centers (in Canada, Spain, South Korea, the Czech Republic, and Turkey) with acute ischemic stroke and intracranial arterial occlusion demonstrated on computed tomographic angiography (CTA). EXPOSURES: Demographics, clinical characteristics, time from alteplase to recanalization, and intracranial thrombus characteristics (location and permeability) defined on CTA. MAIN OUTCOMES AND MEASURES: Recanalization on repeat CTA or on first angiographic acquisition of affected intracranial circulation obtained within 6 hours of baseline CTA, defined using the revised arterial occlusion scale (rAOL) (scores from 0 [primary occlusive lesion remains the same] to 3 [complete revascularization of primary occlusion]). RESULTS: Among 575 patients (median age, 72 years [IQR, 63-80]; 51.5% men; median time from patient last known well to baseline CTA of 114 minutes [IQR, 74-180]), 275 patients (47.8%) received intravenous alteplase only, 195 (33.9%) received intravenous alteplase plus endovascular thrombectomy, 48 (8.3%) received endovascular thrombectomy alone, and 57 (9.9%) received conservative treatment. Median time from baseline CTA to recanalization assessment was 158 minutes (IQR, 79-268); median time from intravenous alteplase start to recanalization assessment was 132.5 minutes (IQR, 62-238). Successful recanalization occurred at an unadjusted rate of 27.3% (157/575) overall, including in 30.4% (143/470) of patients who received intravenous alteplase and 13.3% (14/105) who did not (difference, 17.1% [95% CI, 10.2%-25.8%]). Among patients receiving alteplase, the following factors were associated with recanalization: time from treatment start to recanalization assessment (OR, 1.28 for every 30-minute increase in time [95% CI, 1.18-1.38]), more distal thrombus location, eg, distal M1 middle cerebral artery (39/84 [46.4%]) vs internal carotid artery (10/92 [10.9%]) (OR, 5.61 [95% CI, 2.38-13.26]), and higher residual flow (thrombus permeability) grade, eg, hairline streak (30/45 [66.7%]) vs none (91/377 [24.1%]) (OR, 7.03 [95% CI, 3.32-14.87]). CONCLUSIONS AND RELEVANCE: In patients with acute ischemic stroke, more distal thrombus location, greater thrombus permeability, and longer time to recanalization assessment were associated with recanalization of arterial occlusion after administration of intravenous alteplase; among patients who did not receive alteplase, rates of arterial recanalization were low. These findings may help inform treatment and triage decisions in patients with acute ischemic stroke.
Keywords: výsledek terapie; kombinovaná terapie; fibrinolytika; Male; Combined Modality Therapy; Middle Aged; intravenózní podání; Fibrinolytic Agents; cévní mozková příhoda; trombektomie; Stroke; Aged; Prospective Studies; mužské pohlaví; senioři; ischemie mozku; Tissue Plasminogen Activator; Treatment Outcome; tkáňový aktivátor plazminogenu; senioři nad 80 let; lidé; Computed Tomography Angiography; ženské pohlaví; Humans; Aged, 80 and over; CT angiografie; Administration, Intravenous; Female; lidé středního věku; Thrombectomy; Brain Ischemia; prospektivní studie